TEACHING OF THE NATIONAL SPORTS CENTER OF WRESTLING IN HIGHER EDUCATION - Talipdjanov Alidzhan Akramovich; Akhmedova Nargiza Alidjanovna (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
In this article, the historical development of the national wrestling sport, directions, methods, wrestling, the development of the strength of wrestlers, the main principles of training, the importance of right and left hands in wrestling, the methodology of teaching wrestling, the role of wrestling, sports wrestling, the specific features of sports wrestling are highlighted. improving the training of wrestlers. The long-term structure of the process of training skilled wrestlers is based on the laws of objective formation of sports skills characteristic of some types of martial arts. There is a lot of physical evidence that scientifically supports the history of our struggle. For example, from Pajikent found two warrior hero described fresco Sogd of statehood unique monument, that is. Medium young _ Serious mistakes made during many years or years of training, that is, long-lasting structural elements that are difficult to fill in the future, mistakes in the development of individual training. programs or microcycles relatively easily next meaningful the work with overcome.